The universal existence of myodural bridge in mammals: an indication of a necessary function - Nan Zheng (Nature Portfolio, 2017)
Abstract The “myodural bridge” was described in literatures as a dense fibrous tissue connecting the sub-occipital musculature with the spinal dura mater in human studies. Now the concept of “myodural bridge” was perceived as an exact anatomical structure presumably essential for critical physiological functions in human body, and might exist in other mammals as well. To determine the existence of the “myodural bridge” in other mammals and to lay a foundation for the functional study, we examined representatives in five different mammalian orders. Based on the anatomical dissections, P45 plastinated sections and histological sections, we found that a dense fibrous tissue connected the rectus capitisdorsalis minor and the spinal dura mater through the dorsal atlanto-occipital interspace with or without the medium of the posterior atlanto-occipital membrane. These observed connective tissues were very similar to the “myodural bridge” previously described in humans. We proposed that the “myodural bridge”, as an evolutionally conserved structure, presents in many other mammals. Moreover, we believed that the “myodural bridge” might be a homologous organ in mammals. Thus, this study could provide an insight for our understanding the physiological significance of the “myodural bridge”, especially in human.